The Structure of Lobbying and Protection in U.S. Agriculture - Gawande, Kishore (World Bank, Washington, DC, 2012)
The author surveys the empirical literature on the political economy of agricultural protection. He uses a detailed data set of agricultural Political Action Committee (PAC) contributions over five U.S. congressional election cycles over the 1991-2000 period to investigate the relationship between lobbying spending and agricultural protection. A detailed graphical analysis of campaign contributions by the agricultural PACs indicates that although there are very many PACs, in most sectors the majority of contributions are made by very few PACs. Econometric analysis reveals that lobbying spending by agricultural PACs is positively associated with the use of nontariff barriers and specific tariffs by the United States. There is a strong association between the average U.S. tariff on goods that benefit from U.S. export subsidies and lobbying spending. And there is no association between agricultural protection and trade measures such as import penetration and the export-to-output ratio.